The Manual Therapy and Strengthening for the Hip (MASH) Trial: Protocol for a Multisite Randomized Trial of a Subgroup of Older Adults With Chronic Back and Hip Pain. Issue 1 (8th November 2021) - Pugliese, Jenifer M; Coyle, Peter C; Knox, Patrick J; Sions, J Megan; Patterson, Charity G; Pohlig, Ryan T; Simon, Corey B; Weiner, Debra K; George, Steven Z; Piva, Sara; Hicks, Gregory E
Abstract: Objective: Chronic low back pain (CLBP) is a disabling and costly condition for older adults that is difficult to properly classify and treat. In a cohort study, a subgroup of older adults with CLBP who had elevated hip pain and hip muscle weakness was identified; this subgroup differentiated itself by being at higher risk for future mobility decline. The primary purpose of this clinical trial is to evaluate whether a hip-focused low back pain (LBP) treatment provides better disability and physical performance outcomes for this at-risk group compared with a spine-focused LBP treatment. Methods: This study is a multisite, single-blinded, randomized controlled, parallel arm, Phase II trial conducted across 3 clinical research sites. A total of 180 people aged between 60 and 85 years with CLBP and hip pain are being recruited. Participants undergo a comprehensive baseline assessment and are randomized into 1 of 2 intervention arms: hip-focused or spine-focused. They are treated twice weekly by a licensed physical therapist for 8 weeks and undergo follow-up assessments at 8 weeks and 6 months after randomization. Primary outcome measures include the Quebec Low Back Disability Scale and the 10-Meter Walk Test, which are measures of self-report and performance-based physical function, respectively. Impact: This multicenter, randomized clinical trial will determine whether a hip-focused or spine-focused physical therapist intervention results in improved disability and physical performance for a subgroup of older adults with CLBP and hip pain who are at increased risk of mobility decline. This trial will help further the development of effective interventions for this subgroup of older adults with CLBP.